The Geologic Record of Glaciation: Relevance to the Climatic History of Earth - Young, Grant (Geoscience Canada, 1991)
Summary The only long-term record of climatic change is the geologic record, which suggests that the surface of the planet has had a remarkably stable thermal history. This stability is remarkable because of an inferred 30% increase in solar luminosity since Early Archean time. The glacial record provides some of the best evidence of thermal perturbation.The major cause of glaciation may be the periodic reduction of atmospheric C02, which is linked, via plate tectonics, to the weathering cycle. Different glacial epochsmay, however, have had different controls.Early Proterozoic glaciation may have occurred because of the combination of enhanced weathering of newly emergent cratons, and the faint early sun. Associated highly weathered rocks may reflect the high C02 content of the atmosphere. Late Proterozoic glaciation is explained as being due tolowering of atmospheric C02 levels by extreme weathering of a supercontinent at low latitudes. Most Phanerozoic glaciation was caused by the combined effects of weathering of an elevated supercontinent (Pangea) and polar positioning. The Cenozoic glaciation may be related to high latitudes of some continental masses and reduced CO2 levels due to enhanced weathering of the continents which become emergent as the Atlantic Ocean floor ages, cools and sinks. What of the future? In the short term, the "Little Ice Age" climatic cycle suggests warming for about the next 1,000 years. Global cooling should follow as the Earth descends into the next severe glaciation predicted by Milankovitch theory. Anthropogenic contribution to the greenhouse effect should enhance the short-term warming trend. There peated cycle of Cenozoic glaciations will end with the initiation of subduction along the Atlantic margins.